Fuzzy Intelligent Traffic Control System - Sadeghi, Hamid Mir-Mohammad (Eastern Mediterranean University (EMU), 2010)
ABSTRACT: The aim of this thesis is to develop the fuzzy intelligent traffic control system for the optimal controlling of the traffic flow at the traffic intersections. The proposed fuzzy control system is used to effectively manage the urban traffic junction of the intersections of the city Famagusta (Gazimagusa), North Cyprus. The importance of the proposed fuzzy intelligent traffic control system consists in consideration of uncertainty and vagueness of information about the values of the input and output parameters of the system. Using the input parameters and based on the inferences from the fuzzy rules, the fuzzy traffic controller decides how to adjust the extension time of the green phase of traffic lights. The computer simulation is carried out using Matlab software. The optimal extension time of the green phase is determined using the Mamdani inference engine. The effectiveness of the fuzzy traffic controller with four input parameters is explained. Keywords: Fuzzy System, Traffic Control, Fuzzy Logic Controller. …………………………………………………………………………………………………………………………………………………………………………………………………………………… ÖZ: Bu tezin amacı yol kavşağında trafik akışını optimal kontrol etmek için bulanık trafık sistemini geliştirmektir. Önerilen bulanık kontrol sisteminin kullanılmasında amac Kuzey Kıbrıs’ın Gazimağusa şehrinde kentsel trafik kavşağını etkili yönetmekdir. Önerilen bulanık trafik sisteminin önemli özelliği sistemin giriş ve çıkış parametre değerlerinin belirsizlik halinde başarıyla kullanılabilmesinden ibaretdir. Bulanık trafik kontrol sistemi giriş parametrelerini kullanarak ve bulanık kurallardan elde edilen neticeye dayanarak trafik ışıklarının yeşil fazının ayarlanması konusunda karar veriyor. Matlab yazılımını kullanarak bilgisayar simulyasyonu oluşturulmaktadır. Trafik ışıklarının yeşil fazının optimal ayarlanması için Mamdani sonuc çıkarma yöntemi kullanılmaktadır. Dört parametreli bulanık trafik kontrollerin etkinliği açıklanıyor. Anahtar kelimeler: Bulanık Sistem, Trafik Kontrol, Bulanık Mantık Kontroller.
Master of Science in Applied Mathematics and Computer Science. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Arts and Science, Dept. of Applied Mathematics and Computer Science, 2010. Supervisor: Assoc. Prof. Dr. Rashad Aliyev.
Keywords: Applied Mathematics and Computer Science; Traffic Engineering - Computer Systems; Traffic Control - System Design - Fuzzy Systems; Intelligent Control Systems; Fuzzy System - Traffic Control - Fuzzy Logic Controller